Peran Jurnalistik Ma’had Attahdzib (JMA) Dalam Upaya Mengasah Kecerdasan Linguistik Dan Spiritual Santri Di Pesantren Attahdzib Rejoagung Ngoro Jombang - Rosyadi, Moch Ilham; Kibtiyah, Asriana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is determining the Role of Journalistic Ma'had Attahdzib (JMA) in Efforts to Sharpen the Linguistic and Spiritual Intelligence of Santri at the Attahdzib Islamic Boarding School, Rejoagung Ngoro, Jombang. The research methodology used is a type of qualitative research with a case study approach that focuses on the Ma'had Attahdzib Journalistic extracurricular program (JMA). The data collection technique is with observation (observation), interviews and documentation. Data analysis consisted of domain analysis (domain analysis) and taxonomic analysis (taxonomyanalycis). Checking the validity of the data is carried out by extending the research process, carrying out observational persistence, and transferability, dependence and certainty, namely checking the certainty in the data or findings by confirming the actual situation. shows that the Ma'had Attahdzib (JMA) Journalistic extracurricular program can hone the linguistic and spiritual intelligence of students. It is seen from the results of the development of students who are increasingly diligent in reading, writing, reasoning and memorizing after participating in this program. Daily evaluations, halaqoh, mujahadah, takror are factors in increasing the linguistic and spiritual intelligence of students. The supporting factors for this program are the intention and enthusiasm of the students to take part in the program, competent coaches and adequate facilities.